Solar Power Elektrokoagulasi dengan Sistem Aliran Menerus untuk Pengolahan Air Baku - Iskandar Zulkarnain (Jurnal Ilmiah Teknik Pertanian - TekTan, 2019)
Electrocoagulation is the process of clumping and deposition of fine particles that dissolve in water without chemicals used. This process is the best alternative for removing turbidity in processing raw water because the treated water leaves no residue of sufat and chloride. Several studies have been conducted related to the use of the best electrodes, distance and number of electrodes and contact time. The objective of this research to design a solar power electrocoagulation device with a continuous system to be applied in the raw water treatment process on a laboratory scale by observing turbidity, TSS and pH.Â Keywords: electrocoagulation, raw water, turbidity.